WANGUN JEUNG FUNGSI KALIMAH DINA TARJAMAH SURAH AR-ROHMAN PIKEUN BAHAN PANGAJARAN NARJAMAHKEUN DI SMA - Fatah, Ahmad (2017)
This research is motivated by the necessity to open the structure of sentence in Ar-Rahman translation. Because of that, the aim of this research is to know the form and the function in Ar-Rahman translation and the material which is made for learning in Senior High School. The method which is used in this research is descriptive method. The data is collected through literature study technique. The result of this research fine 50 data sentences in Ar-Rahman translation which is analized the form aspect, kind of sentences, structure, and function. Based on the form sentence composed from perfect sentence and imperfect sentence. Perfect sentence, there are 2 simple sentences, 4 wide sentences, 2 compound sentences, and 23 compound-complex sentences. Imperfect sentence, there are 5 elliptical sentences, 10 sequential sentences, 2 marginal sentences, and 2 vocative sentences. Based on the kind of sentence there are verbal sentence and non verbal sentence. The sentences which has verb as predicate the look from amount of followers in Ar-Rahman translation are 12 monotransitive sentences, 1 bitransitive sentence, 1 semitransitive sentence, and 22 transitive sentences. The sentences which has verb as predicate the look from the relation between subject and its predicate. There are 12 active sentences, 5 pasive sentences, 5 medial sentences, and 11 eksistive sentences. While the kind of sentence which has non verb as predicate in Ar-Rahman, there are 5 noun sentences, 6 adjective sentences, and 1 nominal sentences. In Ar-Rahman translation there are 8 structure of sentence, which has or has not variation. Beside that, in Ar-Rahman translation also has the function of sentence. There are declarative sentences, question sentences, and appeal sentences. Afterwords, it is became learning material for translating in Senior High School. This research can improve the knowledge about the structure in Ar-Rahman. The suggestion in this research is pointed to the university students, teacher, goverment, and department of education.----- Penelitian ini dilatarbelakangi oleh perlunya membuka susunan kalimat dalam tarjamah surat Ar-Rahman. Oleh sebab itu, penelitian ini bertujuan untuk mengetahui bentuk dan fungsi kalimat dalam terjemah surat Ar-Rahman serta bahan ajar yang dibuat untuk pembelajaran menerjemahkan di SMA. Penelitian ini menggunakan metode deskriptif. Data yang dikumpulkan melalui teknik studi pustaka. Hasil penelitian menemukan 50 data kalimat dalam terjemah surat Ar-Rahman yang dianalisis dari segi bentuk, warna, pola, dan fungsi kalimat. Dari segi bentuk kalimat terdiri dari kalimat sempurna dan kalimat tidak sempurna. Kalimat sempurna terdiri dari 2 bentuk kalimat tunggal sederhana, 4 bentuk kalimat tunggal luas, 2 kalimat majemuk setara, dan 23 kalimat majemuk bertingkat. Kalimat tidak sempurna terdiri dari 5 kalimat eliptis, 10 kalimat sekuensial, 2 kalimah marginal, dan 2 kalimat singkat. Dari segi warna kalimat terdiri dari 2 yaitu kalimat yang berpredikat kata kerja dan kalimah yang berpredikat bukan kata kerja. Kalimat yang berpredikat kata kerja jika dilihat dari jumlah pendampingnya dalam terjemah surat Ar-Rahman terdiri dari 12 kalimat monotransitif, 1 kalimat bitransitif, 1 kalimat semitrnasitif, 22 kalimat intransitif, dan 1 kalimat semiintansitif. Kalimat yang berpredikat kata kerja, jika dilihat dari hubungan subjek-prédikatnya terdiri dari 12 kalimat aktif, 5 kalimat pasif, 5 kalimat medial atau refleksif, dan 11 kalimat eksisitif. Sedangkan warna kalimat yang berpredikat bukan kata kerja dalam surat Ar-Rahman terdiri dari 5 kalimat benda, 6 kalimat sifat, dan 1 kalimat bilangan. Dalam terjemah surat Ar-Rahman terdapat 8 pola kalimat. Pola tersebut ada yang memiliki variasi, ada juga yang tidak memiliki variasi. Selain itu, dalam surat Ar-Rahman juga terdapat fungsi kalimat yaitu kalimat deklaratif, kalimat tanya, dan kalimat seruan. Selanjutnya, hal tersebut dijadikan sebagai bahan pembelajaran menerjemahkan di SMA. Penelitian ini bisa menambah wawasan tentang susunan kalimat dalam surat Ar-Rahman. saran dalam penelitian ini ditujukan kepada mahasiswa, guru, pemerintah, dan lembaga-lembaga pendidikan.